ANALISIS KARAKTER MANDIRI SISWA PADA MATA PELAJARAN EKONOMI DI MADRASAH ALIYAH NURUL HIDAYAH BANTAN - Ummi Mawaddah Alfitri, Ristiliana, Salmiah, (SJEE (Scientific Journals of Economic Education), 2019)
Abstract This study aims to determine the Independent Character of Students in Economic Subjects in Madrasah Aliyah Nurul Hidayah Bantan. This research is motivated by the existence of students who postpone the completion of the task ahead of the deadline given by the teacher, there are students who are not confident with the results of their work, there are students who are not able to do the tasks given by the teacher, there are students who are afraid of facing the risks of the choices already made take it, tend to fear failure, there are many students who are less able to solve their own problems, which he faces during the teaching and learning process. This research is a qualitative research. The subjects in this study were 61 social studies class X students and 2 economics teachers as well as research informants and the object of this study was the students' independent character. Data collection techniques using questionnaires, interviews, and documentation. The data analysis technique used in this study was a descriptive qualitative analysis with a percentage. Based on the results of research and data analysis that the Character of Independent Students in Economic Subjects in Madrasah Aliyah Nurul Hidayah Bantan Overall can be categorized well with a percentage of 36.29%. The 63.29% data is categorized in the range of values of 61% -80%. Keywords : Student Independent Character